(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
In today’s digital world where there is an endless variety of content consumed such as books, videos, articles, Films, etc., finding material of one’s choice has become an infallible task. Digital content on the other hand Providers want to engage more and more users in their service for maximum time. Where is it the recommender system comes into picture where content providers advise users by content User choice in this paper we have proposed a movie recommendation system .Purpose of movie recommendation system aims to provide users with accurate movie recommendations. Usually basic recommendation system to make recommendations consider one of the following factors; User preference known as content based Filtering or the preference of similar users known as collaborative filtering. To create a stable and accurate recommender system will use of content based filtering.